Evaluation of immunogenicity post two doses of inactivated SARS-CoV-2 vaccine, Covaxin after six months - Rima R. Sahay; Pragya D. Yadav; Ashok Nandapurkar; Rutuja Dhawde; Annasaheb Suryawanshi; Deepak Y. Patil; Anita M. Shete; Gajanan N. Sapkal; Milind Kulkarni; Yogesh K. Gurav; Gururaj R. Deshpande; Jagdevi S. Ghodke; et al. (Taylor & Francis Group, 2022)
We have evaluated the immunogenicity of two dose of Covaxin given at a one-month interval to two adult populations, i.e. COVID-19 naïve-vaccinated individuals (n = 118) and COVID-19 recovered individuals (n = 128) with the vaccination. The immune response in the study population were assessed at three follow-ups, namely at one month post first dose, one and six months after the second dose. The persistence of S1RBD IgG and neutralizing antibodies for six months post vaccination was observed at different time intervals. The enhanced immune response was observed in both the participant groups. The study emphasizes the need for a booster dose post six months of vaccination.